2007
DOI: 10.1088/1751-8113/40/9/012
|View full text |Cite
|
Sign up to set email alerts
|

On a complementary scale of crystal-field strength

Abstract: A new measure of the crystal-field strength, complementary to the conventional one, is defined. It is based on the rotational invariants |B k0 | av or | k B k0 | av , k = 2, 4, 6, of the crystal-(ligand)-field (CF) Hamiltonian H CF parametrizations, i.e. on the axial CF parameters modules averaged over all reference frame orientations. They turn out to be equal to H (k) CF av and |H CF | av , respectively. While the traditional measure is established on the parametrization modules or on the second moment of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 27 publications
0
46
0
1
Order By: Relevance
“…The asphericity A k for and 6 of any electronic state may serve as a reliable measure of its capability for CF splitting produced by the [10,13,14]   2 = 1 2 1 ,…”
Section: The Asphericity Of An Electron Eigenstate and Its Crystal-fimentioning
confidence: 99%
See 1 more Smart Citation
“…The asphericity A k for and 6 of any electronic state may serve as a reliable measure of its capability for CF splitting produced by the [10,13,14]   2 = 1 2 1 ,…”
Section: The Asphericity Of An Electron Eigenstate and Its Crystal-fimentioning
confidence: 99%
“…The k A magnitudes and their possible variations due to the J-mixing of the RS states are thoroughly discussed. An inseparable entanglement of the asphericities k A and the k-components of the CF strength k [9][10][11][12][10,13,14], resulting from the orthogonality of the 3-j symbols [3,4] (Equation (1) …”
Section: Introductionmentioning
confidence: 99%
“…Besides, when Dy 3 þ is situated at a low symmetry site (without inversion symmetry), the 4 F 9/2 -6 H 13/2 transition emission is dominant in the visible emission spectrum; when Dy 3 þ is at a high symmetry site (with inversion symmetry), the 4 F 9/2 -6 H 15/2 transition emission is prominent [32,33]. The yellow emission ( 4 F 9/2 -6 H 13/2 ) corresponds to the hypersensitive (forced electric dipole) transition with the selection rule ΔJ¼2 (J: the angular momentum), which is strongly dependent on the chemical environment surrounding Dy 3 þ ions [34,35]. It can be seen from the Fig.…”
Section: Photoluminescence Properties Of the Ca 20 Mg 3 Al 26 Si 3 O mentioning
confidence: 99%
“…It was observed that PL intensity increases up to 3 mol% Dy 3+ ions and beyond this, the intensity decreases due to concentration quenching. Concentration quenching may occur due to two reasons: (i) the distance between the ions shortens and the interaction of the ions becomes stronger, thus producing energy transfer interaction; (ii) it may be due to crossrelaxation 13,14 . The resultant CIE coordinates were estimated by utilizing the PL emission spectrum.…”
mentioning
confidence: 99%